The women's war of 1929 : gender and violence in colonial Nigeria. - Matera, Dr Marc (Palgrave Macmillan, 2011)
In 1929, tens of thousands of south eastern Nigerian women rose up against British authority in what is known as the Women's War. This book brings togther, for the first time, the multiple perspectives of the war's colonized and colonial participants and examines its various actions within a single, gendered analytical frame.